Pengaruh Motivasi Kerja Intrinsik dan Ekstrinsik terhadap Kinerja Karyawan PT. Citra Andalan Rasa - Fira Firnanda; Isabella, Astrid Aprica; Novalita Novalita (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of Intrinsic and Extrinsic Work Motivation on employee performance at PT. Citra Andalan Rasa. Intrinsic Work Motivation includes drives that come from within employees, such as the desire to succeed, future hopes, and personal satisfaction, while Extrinsic Work Motivation includes external factors such as the work environment, leadership, and appreciation. PT. Citra Andalan Rasa is a souvenir company in Lampung Province that faces challenges in the form of fluctuations in monthly sales targets and mismatches in work responsibilities, which have the potential to reduce employee performance. The type of data in this study uses quantitative research using primary and secondary data. In this study, a saturated sampling technique was used to determine the research sample because it has a population of less than 100 or the entire population is used as a sample, so the determination of the sample for this study was 36 respondents. The analysis technique used was through Validity Test, Reliability, Multiple Linear Regression, Classical Assumptions, and Hypothesis. From the results of the research that has been done, it shows that Intrinsic and Extrinsic Work Motivation have a significant effect together on Employee Performance at PT. Citra Andalan Rasa.  Intrinsic and extrinsic motivation account for 92% of employee performance at PT Citra Andalan Rasa. The remaining 8% is influenced by other factors not examined in this study.